Familial 18q12.2 deletion supports the role of RNA‐binding protein CELF4 in autism spectrum disorders. Issue 6 (13th April 2017) - Barone, Rita; Fichera, Marco; De Grandi, Mariaclara; Battaglia, Marta; Lo Faro, Valeria; Mattina, Teresa; Rizzo, Renata
Abstract : Deletion of 18q12.2 is an increasingly recognized condition with a distinct neuropsychiatric phenotype. Twenty‐two patients have been described with overlapping neurobehavioral disturbances including developmental delay, intellectual disability of variable degree, seizures, motor coordination disorder, behavioral/emotional disturbances, and autism spectrum disorders. The CUGBP Elav‐like family member 4 ( CELF4) gene at 18q12.2 encodes a RNA‐binding protein that links to RNA subsets involved in pre‐ and postsynaptic neurotransmission including almost 30% of potential autism‐related genes. Haploinsufficiency of CELF4 was associated with an autism or autistic behavior diagnosis in two adult patients with de novo 18q12.2 deletions. We report on a girl and her mildly affected mother with a 275 kb deletion at 18q12.2 involving CELF4 and KIAA1328 whose disruption is not associated with any known disease. The child was diagnosed with syndromic intellectual disability and autism at 6 years of age. Her mother had minor dysmorphisms, mild intellectual disability, and autistic behavior. The deleted region reported in this family is one of the smallest so far reported at 18q12.2. This is also the first full clinical description of maternally inherited CELF4 haploinsufficiency. The present study refines the molecular and neuropsychiatric phenotype associated with 18q12.2 deletion leading to CELF4 haploinsufficiency and provides evidence for a role for CELF4 in brain development and autism spectrum disorders.